Building healthcare provider relationships for patient-centered care: A qualitative study of the experiences of people receiving injectable opioid agonist treatment - Marchand, Kirsten (Subst Abuse Treat Prev Policy, 2020)
BACKGROUND: Injectable opioid agonist treatment (iOAT) was designed as a pragmatic and compassionate approach for people who have not benefitted from medication assisted treatment with oral opioids (e.g., methadone). While, a substantial body of clinical trial evidence has demonstrated the safety and effectiveness of iOAT, considerably less is known about the patient-centered aspects of this treatment and their role in self-reported treatment goals and outcomes. The aim of this study was to explore participants’ experiences in iOAT as they broadly relate to the domains of patient-centered care. A secondary goal was to explore how these experiences affected participants’ self-reported treatment outcomes. METHODS: A qualitative methodology, and constructivist grounded theory approach, was used to guide sampling, data collection and analysis. A total of 30 in-depth interviews were conducted with people receiving iOAT in North America’s first clinic. Audio-recordings for each semi-structured interview were transcribed and read repeatedly. The strategy of constant comparison was used through iterative stages of line-by-line, focused and theoretical coding until theoretical saturation was achieved. RESULTS: “Building healthcare provider relationships for patient-centered care in iOAT” was the emergent core concept. Healthcare provider relationships were established through two interrelated processes: ‘Opening up’ was attributed to the positive environment, and to feeling understood and supported by healthcare providers. ‘Being a part of care’ emerged as participants felt safe to ask for what was needed and had opportunities to collaborate in treatment decisions. These processes established a foundation in which participants experienced care that was responsive to their individual dose, health and psychosocial needs. CONCLUSIONS: The core concept suggested that therapeutic relationships were fundamental to experiences of patient-centered care in iOAT. When relationships were respectful and understanding, participants received individualized and holistic care in iOAT. These findings offer a valuable example of how therapeutic relationships can be strengthened in other substance use treatment settings, particularly when responding to the diverse treatment needs of clients.